Peter Friedl : Domestic. Arbeiten = works 1990-2002. - Landesmuseum, Linz; Beyerle, Tulga; Gohlke, Gerrit; Hochleitner, Martin; Marí, Bartomeu; Spindler, Gabriele (Wien : Triton Verlag Wien, 2002)
The catalogue domestic, for the exhibition of the same name, comprehensively and chronologically documents Peter Friedl's works from 1990 to the present in the form of a handbook. This presention of the works and projects consistently avoids every formulation of a hierarchical genealogy. In addition to the short comments by Raimar Stange, three essays by Tulga Beyerle, Gerrit Gohlke, and Bartomeu Mari deal with issues specific to the works. They investigate, among other things, the critical context of conceptual art, genre theory, institutional critique, music and design.
bibliog. p. 169-176
biog., ind. tent., gr. tent. p. 167-168
Peter Friedl : Domestic, Landesmuseum, Linz, 18. April - 30. Juni 2002
Duits
Engels
boek
Keywords: Friedl, Peter